Assessment of in vitro Antidiabetic Activity of Pterocarpus marsupium and Green Synthesis and Characterization of Silver Nanoparticles Using Its Bark and Wood - J Bagyalakshmi; H Haritha (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
Background: The growth of nanoparticles has a great footprint in recent years. There is increasing optimism that nanotechnology, as applied to medicine, will bring significant advances in the diagnosis and treatment of disease. Objective: The objective of the study was to conduct a Green synthesis of silver nanoparticles from aqueous extract of Pterocarpus marsupium bark and wood and its characterization. As well as an in vitro anti-diabetic study. Methods: The study was conducted using instruments, Magnetic stirrer with hot plate, Magnetic bead, centrifuge (REMI), Shimadzu UV-visible spectrophotometer, IR spectrophotometer, Malvern Zeta size analyser, and scanning electron microscopy. The Pterocarpus marsupium bark and wood were collected from Palakkad, Kerala, India. Synthesis of Pterocarpus marsupium silver nanoparticles was done by drop-wise addition of 1 mM silver nitrate to Pterocarpus marsupium bark and wood extract. Characterization of synthesized nanoparticles was carried out by visual examination, UV-visible absorption spectroscopy, FTIR spectroscopy, Poly dispersity index and Zeta value. In vitro anti-diabetic study for the synthesised silver nanoparticles was carried out by \(α\)-amylase inhibition assay. Results: The result suggested that Pterocarpus marsupium exhibits good \(α\)- amylase inhibition under in vitro conditions The synthesis of silver nanoparticles using Pterocarpus marsupium extract was eco-friendly and cost-effective. Aqueous extract of Pterocarpus marsupium bark and wood extract were mixed with the aqueous solution of silver nitrate. The colour of the solution changes from yellow to brown colour due to the surface Plasmon resonance which is the primary confirmation for the formation of silver nanoparticles. The surface Plasmon band in the silver nanoparticles was found to be 431 nm. The FTIR study concluded that hydroxyl and carboxyl groups act as reducing and stabilizing agents and the phenolic group functions as a capping agent. The average particle size was found to be 148.5 nm. Its polydispersity index was 0.336 and zeta potential was measured and found to be -28 mV with the peak area of 100% intensity. This indicates that the formed nanoparticles were stable. The in vitro anti-diabetic study confirms that Pterocarpus marsupium has anti-diabetic activity. From the FTIR spectral analysis, it is concluded that the hydroxyl and carboxyl groups present may act as reducing and stabilizing agents and the phenolic group present may act as a capping agent. Conclusion: Pterocarpus marsupium silver nanoparticles are found to be effective for anti-diabetic activity. The study found without using any chemical reagent as a stabilizing agent the silver nanoparticles are stable. Hence this cost-effective and eco-friendly method is highly promising for the future.